Characterization of 'basparin A,' a prothrombin-activating metalloproteinase, from the venom of the snake Bothrops asper that inhibits platelet aggregation and induces defibrination and thrombosis - Loría Masís, Gilbert David (2003)
A prothrombin activator, named ‘basparin A,’ was isolated from the venom of the crotaline snake Bothrops asper, the species responsible for the majority of snakebite cases in Central America. It is an acidic (pI 5.4), 70 kDa, single chain P-III metalloproteinase comprising, in addition to the metalloproteinase domain, disintegrin-like, and high-cysteine domains. Basparin A is a glycoprotein displaying immunological cross-reactivity with BaH1, a P-III hemorrhagic metalloproteinase isolated from the same venom. It activates prothrombin through the formation of meizothrombin, without requiring additional cofactors; it is, therefore, a class A snake venom prothrombin activator. In contrast with most venom metalloproteinases, it does not degrade components of the extracellular matrix. Apart from its clotting activity, basparin A inhibits collagen-dependent platelet aggregation in vitro, an effect that does not depend on proteolytic activity. Clotting activity on human plasma is not abrogated by the plasma proteinase inhibitors α2 macroglobulin and murinoglobulin, whereas activity is completely inhibited by Costa Rican polyvalent (Crotalinae) anti-venom. Basparin A does not induce local tissue alterations, such as hemorrhage, myonecrosis, and edema, in mice. Moreover, it does not induce systemic hemorrhage, thrombocytopenia nor prolongation of the bleeding time following intravenous administration. At low doses, the only observed effect induced by basparin A, when injected intravenously or intramuscularly into mice, is defibrin(ogen)ation. At higher doses, intravenous administration resulted in sudden death due to numerous occluding thrombi in pulmonary vessels. Basparin A is likely to play an important role in the coagulopathy associated with B. asper envenoming.